Кырӟамтэ кырӟан - Данилов Григорий Данилович (Удмуртия, 1991)
Экземпляры: ф.3 (1992) / Инвентарный номер: 34994 / Цена: / Сис.шифр: 84(2Рос=Удм)6-4 / Авт.знак: Д 18 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)6-44